Performance Evaluation of Perovskite Solar Module of Wide Range Operating Conditions (Journal of Engineering, 2025)
Solar energy is considered a sustainable and clean source of power. Even so, solar cells face challenges such as the low efficiency of some systems and the need for large installation areas. Therefore, efforts have been directed toward developing technologies like perovskite solar cells to improve efficiency and reduce the need for large spaces. The experimental work was conducted under outdoor exposure in Baghdad, Al-Jaderia. The readings were taken on selected days, where the atmospheric conditions of clear sky. To study the impacts of temperature variations on solar performance, solar irradiance must be kept constant and vice versa. Therefore, to have a temperature range and for more accuracy, the measurements were done for the tested module with five solar radiation levels: 200, 400, 600, 800, and 1000 W/m2. The optimum conditions that it have the best performance are achieved when the solar module works at a low ambient temperature. The highest power at solar radiation 1000W/m² was 446.2 mW and at module temperature 43 C°, while the minimum corresponding  64  mW at solar radiation 200W/m2 and module temperature of 43.6 C°. The highest open voltage equals 10.80 V, and at a module temperature of 43 C°, and maximum short current 77 mA at solar irradiance 1000W/m2 and module temperature 58 C°. The best value of fill factor was achieved 0.661 at solar irradiance 200 W/m2 and module temperature 43.6 C°. While the best efficiency value 8.9 % at solar radiation 1000 W/m2, and module temperature 43 C°.